Enacting Christian identities in Catholic colleges and universities: An organizational studies perspective on core practices, challenges, and discernments - Michael G. Pratt (Church, Communication and Culture)
It is not enough for Catholic universities to simply profess having a Christian identity. This identity needs to be enacted throughout the organization via students, faculty, staff, and administrators. Because identity has different foundations, such as groups, roles, material artifacts, and stories, there are a variety of ways a Christian identity can be lived out in a Catholic university. However, despite these many avenues for enacting identity, such enactment comes with several challenges. At the heart of most of these challenges is the fact that Catholic universities have other identities beyond a Christian one. This paper addresses not only how identity can be enacted, but highlights the challenges to such identity enactment and the trade-offs they present for discernment.